OVERVIEW OF THE SUPPORT SYSTEM OF IMPLEMENTATION OF THE FCC: FAMILY, NURSE, AND THE HOSPITAL ENVIRONMENT - Eva Supriatin; Diwa Agus Sudrajat; Fitri Nurhayati; Linlin Lindayani (Jurnal Ilmiah Kesehatan Keperawatan, 2021)
The concept of family-centered care (FCC) in nursing practice, the attentive treatment of families, the dissemination of information to families in order to understand the condition and treatment, and including participation of parents in decision-making and treatment through cooperation of parents and nurses. Environmental support for hospital is needed in the deployment of FCC services. The aim of this study was to describe Family-Centered Care: Family, Nurse and Hospital Environment in RS. Dustira Kindergarten II. This study is a descriptive quantitative study conducted in July 2019, including 22 nurses and 37 children's parents in the inpatient unit with a total sampling technique. Analysis of information using questionnaires and analysis of data using frequency distribution. This study shows that family-centered care services based on support to parents showed that all parents (86.5 %) got good support. Services Family-Centered Review purpose on the role of nurses showed that all nurses (95.5 %) responded well and how more than half of the respondents (54.1 %) perceived family-Centered Care as a supportive environment. Supposed to support the harmony among households, nurses and hospitals is expected to create a family-centered care service (FCC). The hospital needs to improve facilities for enhanced comfort and healing of hospitalized children.